Adaptive rolling plans good - Maćkowiak, Piotr (Uniwersytet Ekonomiczny we Wrocławiu, 2010)
0BHere we prove the goodness property of adaptive rolling plans in a multisector optimal growth model under decreasing returns in deterministic environment. Goodness is achieved as a result of fast convergence (at an asymptotically geometric rate) of the rolling plan to balanced growth path. Further on, while searching for goodness, we give a new proof of strong concavity of an indirect utility function – this result is achieved just with help of some elementary matrix algebra and differential calculus.
Argumenta Oeconomica, 2010, Nr 2 (25), s. 117-136
Keywords: indirect utility function; adaptive rolling planning; multisector model; goog plans